Developing Female-Genital Infection Preventive Behavior Tool (FGIPBT) for Islamic Boarding School Population Based on The Integrated Behavior Model - Kanthi Devi Ayuningtyas; Ika Agustina; Ita Noviasari (STIKes Patria Husada Blitar, 2021)
Female-genital infection in adolescence causes discomfort and may develop into a serious issue. Islamic boarding school female students are a population at risk of getting a female-genital infection due to the lack of hygiene practice sum up with the lack of parental control. Prevention of female-genital infection through behavioral change is mandatory but the changes in behavior are not an effortless thing. There are underlying constructs that predispose the behavior as described in the Integrated Behavior Model (IBM). Dealing with those constructs will facilitate the change of behavior. However, there was no exact tool for assessing construct that determines the female-genital infection preventive behavior, especially for Islamic boarding school female-student population. That was the major reason for the Female-genital Infection Preventive Behavior Tool (FgIPBT) development. We generated a tool based on IBM constructs and the Indonesian Society of Dermatology and Venereology (INSDV) recommendation regarding genital infection preventive behavior. A deductive method of item generation, expert judgments, and internal consistency test involved 143 female-student from 3 different Islamic boarding schools was done to generate a valid and reliable tool. Total 177 valid items composed on the first phase and two different arrangements of items has subjected the reliability on the second phase. Items that were arranged based on behavior items and assessed every IBM construct (Type 1) had higher reliability value than items that were arranged based on IBM construct for all behavior items (Type 2). Assessing different construct for each point of behavior at the same time generate more reliable data than assessing the same construct for all points of behavior.